Myeloid Cell Classification and Therapeutic Opportunities Within the Glioblastoma Tumor Microenvironment in the Single Cell-Omics Era - Larkin, Collin J.; Arrieta, Víctor A.; Najem, Hinda; Li, Gongbo; Zhang, Peng; Miska, Jason; Chen, Peiwen; James, Charles David; Sonabend, Adam M.; Heimberger, Amy B. (Frontiers in Immunology, 2022)
Gliomas are composed of multiple distinct cell populations, each playing a unique role within the tumor microenvironment (TME). Each of these cell types contains a spectrum of subtypes that increase the level of heterogeneity and complexity of these tumors. In this context, antagonistic forces promoting both tumor growth and suppression exist in the TME that influence clinical outcomes and responses to therapies. Initiatives such as The Cancer Genome Atlas (TCGA) and the GLASS consortium (1), have provided important information about the genetic variation and evolution among gliomas, leading to the molecular classification for glioblastoma (GBM) (2). However, since bulk genomic and transcriptome data averages the genetic alterations and gene expression patterns, respectively, of individual tumors, the analysis of such data has limits regarding determining the extent of cell subpopulation heterogeneity within a tumor and thus response to therapeutic interventions. In contrast, technologies such as single-cell RNA-seq (scRNA-seq) and cytometry by time-of-flight (CyTOF) are enabling the high-resolution characterization of glioma cellular heterogeneity (3). Single cell analysis is proving informative about cell subpopulations in normal tissues and in treated recurrent GBM, with the latter providing insights regarding therapy-driven tumor evolution (4, 5). It is anticipated that single cell analyses will ultimately prove informative regarding the individualization of glioma patient treatment based on knowledge of a tumor’s cellular heterogeneity combined with increased understanding of cell subpopulation interactions. The myeloid compartment is the predominant subset of immune cells within the GBM microenvironment (6). This myeloid-rich environment is a hallmark of GBM, and these cells exert pro- and anti-tumor influence under different circumstances (6-8). Advances in understanding of glioma cellular heterogeneity from single cell analyses have exemplified the over-simplistic nature of the historically proposed pro-inflammatory M1 and immune suppressive M2 categories. Changes to the M1/M2 classification have been proposed by others, but without the benefit of single cell characterization data (9). In this review, we discuss the current myeloid classification and its shortcomings, as well as how emerging single-cell technologies can be leveraged for increased understanding of glioma-infiltrating myeloid cell function in addition to impacting clinical outcomes in glioma patients.